Role of tissue engineering in oral & maxillofacial surgery – a review - Angeline L, Reenu; T., Rohini; Balasubramaniam, Saravanan (International Journal of Medical Research and Review, 2019)
Tissue engineering can be defined as the “reconstitution of tissue and organs, in vitro for use as model systems in basic and applied research, or for use as grafts to replace damaged or diseased body parts or body functions”. Biomaterials have been used as replacement tissues and grafts have been used to reconstruct defects in craniofacial region till Uristmade the first attempt of producing exogenous bone with the help of bone morphogenetic proteins. The success of tissue engineering over the field of all transplantation is that conceptually a three-dimensional functional tissue is designed. This field has become a boon to the Cranio Maxillofacial surgeons and has provided them with a supplement to existing treatment for reconstruction of Oral & Craniofacial region. The purpose of this article is to present an overview of the various uses of tissue engineering in the field of Oral and Maxillofacial Surgery.